Peran Manajemen Pengetahuan dan Keterampilan terhadap Inovasi Produk pada Empu Keris di Kabupaten Sumenep - Moh. Kurdi; Unsul Abrar; Syaiful Anwar (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
The making of kris in Sumenep Regency is a cultural heritage that is not only firmly rooted in historical values, but also faces modern challenges in the form of changing consumer preferences. This study aims to analyze the influence of knowledge and skill management on product innovation by keris masters. Using quantitative methods through regression analysis, the study found that skills had a significant positive influence on product innovation, while knowledge management showed a significant negative influence. This shows that the success of product innovation is highly dependent on the application of practical skills and the appropriate management of knowledge. These results are an important basis for the development of local culture-based innovation strategies in the traditional creative industry sector.